1996
DOI: 10.1021/ic960632f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tungsten (1-Pyridinio)imido Complexes:  Facile N−N Bond Cleavage To Form Pyridine from Coordinated Dinitrogen1

Abstract: Tungsten hydrazido complexes [WCl2(NNH2)(L)(PMe2Ph)2] (L = CO, C2H4) derived from dinitrogen complex [W(N2)2(PMe2Ph)4] reacted with 2,4,6-trimethylpyrylium or 2,6-diethoxycarbonyl-4-phenylpyrylium tetrafluoroborate to give novel (1-pyridinio)imido complexes in high yields, which were spectroscopically and crystallographically characterized. The (2,4,6-trimethylpyridinio)imido complexes [WCl2(NNC5H2Me3)(L)(PMe2Ph)2][BF4] underwent facile and selective N−N bond cleavage upon treatment with KOH or cobaltocene at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In contrast, the N−N bond lengths in complexes 3a − c are 1.363(3) Å, 1.364(3) and 1.361(3) Å, and 1.367(5) Å, respectively, and can be regarded as in the range of N−N single bonds. These values are similar to that found in the (1-pyridinio)imido complex [WCl 2 (NNC 5 H 2 Me 3 -2,4,6)(CO)(PMe 2 Ph) 2 ][OTf] (1.366(10) Å; OTf = OSO 2 CF 3 ), and slightly shorter than those in the related hydrazidium complexes [WCl(NNH 3 )(PMe 3 ) 4 ]Cl 2 (1.396(20) Å), [Cp*MoMe 3 (NNMe 3 )][OTf] (1.426(5) Å),4b and [Cp*TaS(SBu t )(NNMe 2 Bu t )] (1.46(1) Å) . Complexes 3a − c contain a titanium center coordinated by one Cp (or Cp*), two chlorine atoms, and one imido nitrogen atom, making the complexes monomeric.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In contrast, the N−N bond lengths in complexes 3a − c are 1.363(3) Å, 1.364(3) and 1.361(3) Å, and 1.367(5) Å, respectively, and can be regarded as in the range of N−N single bonds. These values are similar to that found in the (1-pyridinio)imido complex [WCl 2 (NNC 5 H 2 Me 3 -2,4,6)(CO)(PMe 2 Ph) 2 ][OTf] (1.366(10) Å; OTf = OSO 2 CF 3 ), and slightly shorter than those in the related hydrazidium complexes [WCl(NNH 3 )(PMe 3 ) 4 ]Cl 2 (1.396(20) Å), [Cp*MoMe 3 (NNMe 3 )][OTf] (1.426(5) Å),4b and [Cp*TaS(SBu t )(NNMe 2 Bu t )] (1.46(1) Å) . Complexes 3a − c contain a titanium center coordinated by one Cp (or Cp*), two chlorine atoms, and one imido nitrogen atom, making the complexes monomeric.…”
Section: Resultssupporting
confidence: 80%
“…Interestingly, reductive N−N bond cleavage was not observed for [Cp*MoMe 3 (NNMe 3 )][OTf] with zinc-amalgam or cobaltocene, and on the basis of this fact it was suggested that hydrazidium complexes (M⋮N−NH 3 + ) are not intermediates of the most facile N−N bond cleavage reaction path of hydrazine and hydrazido ligands 4b. On the other hand, the N−N bond in the cationic W(IV) complex [WCl 2 (NNC 5 H 2 Me 3 -2,4,6)(CO)(PMe 2 Ph) 2 ][OTf] could be reductively cleaved by cobaltocene (vide supra) . Furthermore, it has been demonstrated by Holm and co-workers that N−N bond cleavage easily takes place in the reaction between TsNNC 5 H 5 (Ts = tosyl) and the Mo(IV) complex [MoO(Et 2 dtc) 2 ] (Et 2 dtc = diethyldithiocarbamate) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 which could be further transformed to free pyridine and ammonia by reaction with KOH. 84 The nucleophilicity of the terminal nitrogen atom in [W(N 2 )(NCS)(dppe) 2 ] − was also leveraged to promote N−C bond formation by S N Ar pathways. Fluoroarenes such as p-FC 6 H 4 CO 2 Me that are activated by complexation to Cr(CO) 3 , [(η 5 -C 5 H 5 )Fe], or [(η 5 -C 5 H 5 )Ru] underwent N−C bond formation and the resulting bimetallic complexes were characterized by X-ray diffraction (Scheme 11).…”
Section: Interaction Of N 2 With Transition Metalsmentioning
confidence: 99%
“…By contrast, the hydrazido derivative [WX 2 (NNH 2 )­(PMe 2 Ph) 3 ] (X = Cl or Br) underwent further functionalization with phthalaldehyde to generate the corresponding (phthalimidin-2-yl)­imido complexes . In addition, treatment with pyrilium compounds produced (1-pyridinio)­imido complexes which could be further transformed to free pyridine and ammonia by reaction with KOH …”
Section: N–x Bond Formation With Retention Of the N–n Bondmentioning
confidence: 99%